Molecular phylogenetic analysis of the family Macromiidae (Odonata) worldwide based on a mitochondrial and two nuclear markers, with a short overview of its taxonomic history - Kosterin, Oleg E.; Vierstraete, Andy; Schneider, Thomas; Kompier, Tom; Hu, Fang-Shuo; Jr., Larry Everett; Makbun, Noppadon; Onishko, Vladimir V.; Papazian, Michel; Dumont, Henri J. (Zootaxa, 2025)
Three molecular markers (two traditional and a new one), the barcoding fragment of the mitochondrial COI gene, the nuclear ITS region of the nucleolus organiser, and the nuclear histone H3–H4 region including partial sequences of the highly conserved genes of core histones H3 and H4 and the non-coding spacer between them, were sequenced in 38 (31% of all) species of Macromiidae, representing all its four genera. Besides, 15 species of the related incertae sedis genera Macromidia Martin, 1907, Idionyx Hagen, 1867 and Oxygastra Selys, 1870 were sequenced. Available sequences of the concerned groups were also adopted from GenBank. All markers resolved Macromiidae as a monophyletic clade with the highest support. In contrast, our markers did not resolve the expected monophyletic branch containing the incertae sedis genera. Didymops transversa (Say, 1840) clustered with Macromia Rambur, 1842 in most trees as an inner lineage in the Macromia cluster. For this reason, we restored the synonymy of Didymops Rambur, 1842 with Macromia. Epophthalmia Burmeister, 1839 and Phyllomacromia Selys, 1878 were resolved as sister branches, as proposed before on morphological basis. On the species level, Macromia fraenata Martin, 1907, Macromia clio Ris, 1916 and Macromia kubokaiya Asahina, 1964 were restored as valid species names. Macromia flavocolorata Fraser, 1922 was downgraded to the subspecies Macromia calliope flavocolorata, stat rev., but the name Macromia miniata Fraser, 1924 was restored as valid species name to denote the species of the Western Ghats of India once considered as M. flavocolorata as well. The synonymy of M. cupricincta Fraser, 1924 and M. berlandi Lieftinck, 1941 at the species level were confirmed but the latter was treated as M. cupricincta berlandi stat. rev. Macromia hamata Zhou, 2003 was synonymised to Macromia manchurica Asahina, 1964. The presence of Epophthalmia vittata Burmeister, 1839 in Indochina as a common species was confirmed. The situation with Macromia callisto Laidlaw, 1922 remains obscure.